Peripubertal changes in circulating antimüllerian hormone levels in girls - Lashen, Hany (Elsevier for the American Society for Reproductive Medicine, 2013)
OBJECTIVE: To identify correlates and longitudinal changes in circulating antimüllerian hormone (AMH) levels as a marker of ovarian primordial follicle recruitment in normal peripubertal girls. DESIGN: Observational study using mixed longitudinal and cross-sectional analyses. SETTING: Not applicable. PATIENT(S): Unselected girls assessed at ages 7–11 years. INTERVENTION(S): None. MAIN OUTCOME MEASURE(S): AMH, inhibin B, and FSH levels were analyzed in blood samples collected at ages 7, 9, and 11 years for longitudinal analyses and at age 8 years for cross-sectional analyses. RESULT(S): In the cross-sectional analysis, AMH levels at age 8 years were lower in pubertal girls (median 25.0 pmol/L, interquartile range [IQR] 16.0–33.9; n = 39) than in prepubertal girls (33.5 pmol/L, IQR 22.3–49.1; n = 342). In prepubertal girls, higher AMH levels were associated with higher inhibin B levels, lower FSH levels, and larger body mass index at age 8 years and subsequently with later age at menarche. AMH levels were unrelated to birth weight or birth length. In the longitudinal analysis, AMH levels increased between ages 7 (median 27.0 pmol/L, IQR 19.2–34) and 9 years (32.0 pmol/L, IQR 26.5–42.7), then declined between 9 and 11 years (26.5 pmol/L, IQR 19–42.25) with high intraindividual correlation in AMH levels between ages 7 and 9 years and 7 and 11 years. CONCLUSION(S): Measurement of circulating AMH and inhibin B levels suggests that the rate of ovarian primordial follicle recruitment increases in the prepubertal years then declines again following the onset of puberty as follicular activity pattern changes.